STUDY ON CHARACTERISTICS OF LAND AREA REFUGEE RELOCATION ERUPTION SINABUNG KARO DISTRICT AS A BASIS FOR LAND USE BASED WATERSHED MANAGEMENT - Abdul Rauf; Rahmawaty; Hadi Wijoyo (Talenta Publisher, 2015)
Study of the characteristics of the land in the area of refugee relocation eruption of MountSinabung intended as a basis for the use of land-based watershed management in the regionhas been carried out in November and December 2014. The study was conducted using asurvey at the site which is administered in the village of Nagara, Pertibi Lama and PertibiTembe Tiga Panah Sub District Karo District. Field observations carried out on the physicalcharacteristics of the land and soil sampling for laboratory testing of physical, chemical andbiological soil. The study also conducted bassed secondary data sourced from the analysis ofvarious thematic maps such geological maps, soil type maps, topographic maps and maps ofwatershed areas. The results showed that the area of Mount Sinabung relocation is in theupstream region of two important watersheds in North Sumatra and Aceh, which WampuWatershed and Singkil Watershed, the dominant topography sloping to undulating located ata height of more than 1,550 m above sea level. Land in refugee relocation sites Sinabungclassified into subgroups Andic Dystropept which has properties (smeary orthixotropic), the soil is very loose (BD <0.8 g / cm3) and high content of organic matter in theupper layers of the soil pH suitable for upland crops, and the number (population) microbesare also high.